WhatsApp-based intervention to promote tea consumption and healthy lifestyle in Indonesian’s adult - Briawan, Dodik; Sefrina, Linda Riski; Dewi, Mira; Rokhmah, Farida Dwi (Alma Ata University Press, 2024)
Background: Tea flavonoids have been shown to reduce Cardiovascular Disease (CVD) risks, and tea consumption might help reduce the problem in the community. Meanwhile, tea consumption among Indonesian people is still rare and in small quantities.Objectives: This research aimed to evaluate the effect of a WhatsApp-based education intervention,